2014
DOI: 10.1016/j.jad.2014.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Neural response to reward anticipation in those with depression with and without panic disorder

Abstract: Background One of the hallmark features of major depressive disorder (MDD) is reduced reward anticipation. There have been mixed findings in the literature as to whether reward anticipation deficits in MDD are related to diminished mesolimbic activation and/or enhanced dorsal anterior cingulate activation (dACC). One of the reasons for these mixed findings is that these studies have typically not addressed the role of comorbid anxiety, a class of disorders which frequently co-occur with depression and have a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 53 publications
2
29
0
Order By: Relevance
“…A number of studies have found reduced activation in various regions of the striatum during reward anticipation among individuals with current depression or individuals at risk for depression (Dichter et al 2009;Forbes et al 2009;Pizzagalli et al 2009;Smoski et al 2009;Gotlib et al 2010;Olino et al 2011Olino et al , 2014Stoy et al 2012;Ubl et al 2015), as well as increased activity in the ACC (Dichter et al 2012;Gorka et al 2014). However, some other studies have found no differences in striatal activation during reward anticipation between healthy individuals and those with current (Knutson et al 2008;Gorka et al 2014) or remitted depression (Dichter et al 2012), although in at least one case it was not clear that any participant showed activity in the striatum during reward anticipation (Chase et al 2013). Further, at least one study found reduced ACC responses during reward anticipation (Chase et al 2013).…”
Section: Reward Anticipationmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have found reduced activation in various regions of the striatum during reward anticipation among individuals with current depression or individuals at risk for depression (Dichter et al 2009;Forbes et al 2009;Pizzagalli et al 2009;Smoski et al 2009;Gotlib et al 2010;Olino et al 2011Olino et al , 2014Stoy et al 2012;Ubl et al 2015), as well as increased activity in the ACC (Dichter et al 2012;Gorka et al 2014). However, some other studies have found no differences in striatal activation during reward anticipation between healthy individuals and those with current (Knutson et al 2008;Gorka et al 2014) or remitted depression (Dichter et al 2012), although in at least one case it was not clear that any participant showed activity in the striatum during reward anticipation (Chase et al 2013). Further, at least one study found reduced ACC responses during reward anticipation (Chase et al 2013).…”
Section: Reward Anticipationmentioning
confidence: 99%
“…The evidence for altered dorsal ACC responses is also intriguing. In recent work, Shankman and others have posited the hypothesis that this increased activation may actually reflect "conflict" that individuals with depression experience when asked to anticipate processing hedonically positive stimuli that conflict with their current negative internal state (Gorka et al 2014). If so, this would suggest that altered ACC activation is an outcome of the phenomenology of depression rather than potentially playing a causal role in anticipatory pleasure impairments.…”
Section: Reward Prediction Errormentioning
confidence: 99%
“…Although the aINS has not traditionally been considered a key node of the neural reward circuit (Haber & Knutson, 2010), studies have reported aINS activation during reward tasks (Ernst et al, 2004;Gorka, Huggins, Fitzgerald, Nelson, Phan, & Shankman 2014), which is consistent with its broad role in interoceptive awareness and subjective future-oriented states (Craig, 2009(Craig, , 2011. It has also been demonstrated that IU is positively correlated with bilateral anterior and middle insula activation during the viewing of ambiguously angry and happy faces (i.e., two appetitive emotions; Simmons, Matthews, Paulus, & Stein, 2008).…”
mentioning
confidence: 74%
“…These, however, reported intact, if do not increased differential conditioning as indicated by increased skin conductance responses for patients with a major depressive disorder (Nissen et al, 2010), which parallel the present results on a behavioral level. A recent study on primary depressed patients with or without a comorbid panic disorder provided preliminary support for the role of hyperactive dorsal ACC functioning in reduced reward anticipation in major depression as a core pathophysiological feature of affective disorders (Gorka et al, 2014). They also indicated that comorbid anxiety may alter the association between MDD and neural responding to reward anticipation.…”
Section: Discussionmentioning
confidence: 98%